2001
DOI: 10.1046/j.1365-2958.2001.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquirement of cold sensitivity by quadruple deletion of the cspA family and its suppression by PNPase S1 domain in Escherichia coli

Abstract: SummaryEscherichia coli contains a large CspA family, CspA to CspI. Here, we demonstrate that E. coli is highly protected against cold-shock stress, as these CspA homologues existed at approximately a total of two million molecules per cell at low temperature and growth defect was not observed until four csp genes (cspA, cspB, cspE and cspG) were deleted. The quadruple-deletion strain acquired cold sensitivity and formed filamentous cells at 158C although chromosomes were normally segregated. The coldsensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
213
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(226 citation statements)
references
References 35 publications
12
213
0
1
Order By: Relevance
“…In E. coli, the deletion of single csp genes did not result in an obvious phenotype, possibly due to back-up mechanisms based on the presence of closely related CSPs (Xia et al, 2001). In B. bronchiseptica, we investigated the phenotypic effects of mutations in the cspB and cspC genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In E. coli, the deletion of single csp genes did not result in an obvious phenotype, possibly due to back-up mechanisms based on the presence of closely related CSPs (Xia et al, 2001). In B. bronchiseptica, we investigated the phenotypic effects of mutations in the cspB and cspC genes.…”
Section: Resultsmentioning
confidence: 99%
“…Even the production of knock-out mutants did not contribute much to the understanding of their specific function, possibly because of compensatory effects by related cold-shock proteins. For example, in Bacillus subtilis all three csp genes must be deleted to obtain a lethal phenotype (Graumann et al, 1997), while four out of nine csp genes had to be inactivated before a coldsensitive phenotype was achieved in E. coli Xia et al, 2001). In contrast to these data, the single cspB deletion in B. bronchiseptica led to a growth-impaired phenotype at low (15 u C) and elevated temperature (37 u C).…”
Section: Discussionmentioning
confidence: 99%
“…CSPs, which consist of a 5-stranded anti-parallel ␤-barrel (32), share structural similarity to the S1 domains found in PNPase and the ribosomal protein S1 and have been shown to melt out mRNA secondary structures that form at lower temperatures (33). Xia and Inouye (34) reported that a quadruple deletion of 4 of the 9 CSPs rendered E. coli cold-sensitive, and that overexpressing any 8 of the 9 CSPs or the S1 domain from E. coli PNPase alone enabled the quadruple-deleted strain to grow in the cold. Thus, several proteins with bona fide S1 domains as well as proteins that resemble S1 domains (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli CspA binds to ssDNA/RNA without apparent sequence specificity and has been proposed to function as an RNA chaperone that facilitates efficient translation at low temperature (22). Two internal highly conserved consensus RNA-binding motifs (RNP-1 and RNP-2) are critical for CSD nucleotide binding activity (41). A recent paper reported that the CspA protein family acts as transcription anti-terminators and regulates mRNA levels of cold-induced genes in the metY-rpsO operon (23).…”
Section: Discussionmentioning
confidence: 99%